Effects of dietary almond- and olive oil-based docosahexaenoic acid- and vitamin E-enriched beverage supplementation on athletic performance and oxidative stress markers. Issue 12 (14th November 2016) - Capó, X.; Martorell, M.; Busquets-Cortés, C.; Sureda, A.; Riera, J.; Drobnic, F.; Tur, J. A.; Pons, A.
Abstract : Functional beverages based on almonds and olive oil and enriched with α-tocopherol and docosahexaenoic acid (DHA) could be useful in modulating oxidative stress and enhancing physical performance in sportsmen. Abstract : Functional beverages based on almonds and olive oil and enriched with α-tocopherol and docosahexaenoic acid (DHA) could be useful in modulating oxidative stress and enhancing physical performance in sportsmen. The aim of this work was to evaluate the effects of supplementation with functional beverages on physical performance, plasma and erythrocyte fatty acids' and polyphenol handling, oxidative and nitrative damage, and antioxidant and mitochondrial gene expression in young and senior athletes. Athletes performed maximal exercise tests before and after one month of dietary supplementation and blood samples were taken immediately before and one hour after each test. The beverages did not alter performance parameters during maximal exercise. Supplementation increased polyunsaturated and reduced saturated plasma fatty acids while increasing the DHA erythrocyte content; it maintained basal plasma and blood polyphenol levels, but increased the blood cell polyphenol concentration in senior athletes. Supplementation protects against oxidative damage although it enhances nitrative damage in young athletes. The beverages enhance the gene expression of antioxidant enzymes in peripheral blood mononuclear cells after exercise in young athletes.